2010
DOI: 10.1177/159101991001600101
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of ACom Intracranial Aneurysms

Abstract: The immediate and long-term outcomes, complications, recurrences and the need for retreatment were analyzed in a series of 280 consecutive patients with anterior communicating artery aneurysms treated with the endovascular technique. From October 1992 to October 2001 280 patients with 282 anterior communicating artery aneurysms were addressed to our center. For the analysis, the population was divided into two major groups: group 1, comprising 239 (85%) patients with ruptured aneurysms and group 2 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
5
26
1
Order By: Relevance
“…Six studies reported outcomes for unruptured aneurysms,5 9 14–17 and eight included a mix of patients with ruptured and unruptured cases 2 18–24. Twelve studies2 5 9 14 15 17–23 reported treatment outcomes exclusive to ACoA aneurysms, and two studies16 24 incorporated data on aneurysms at other locations. Documentation of the size among the treated aneurysms was highly heterogeneous among studies, and data on size was largely non-extractable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies reported outcomes for unruptured aneurysms,5 9 14–17 and eight included a mix of patients with ruptured and unruptured cases 2 18–24. Twelve studies2 5 9 14 15 17–23 reported treatment outcomes exclusive to ACoA aneurysms, and two studies16 24 incorporated data on aneurysms at other locations. Documentation of the size among the treated aneurysms was highly heterogeneous among studies, and data on size was largely non-extractable.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported outcomes using the GOS,14 16 17 19 23 24 two using the mRS,5 18 and six using qualitative descriptions 2 9 15 20–22. Coil embolization demonstrated high rates of good clinical outcome (EC 99.2%, MC 95.6%, SAC 92.1%; p=0.001), and corresponding low rates of poor clinical outcome (EC 0.8%, MC 4.4%, SAC 7.9%; p=0.001), in comparison with treatment with MC and SAC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,15,16 A limited number of case series have detailed the clinical outcomes, angiographic results, and procedure-related complications specific for endovascular treatment in this location. [10][11][12][13][15][16][17][18][19][20][21][22][23][24] We performed a systematic review of the published literature to better define safety and efficacy profiles for coil embolization of AcomA aneurysms beyond single-center experiences.…”
mentioning
confidence: 99%
“…14,15 Most reported large series of outcome in either intracranial aneurysms coiling or in ACoAAs coiling did not reflect or refer to using this method of ACoA occlusion specifically. [17][18][19] This is because most ACoAAs could be well treated with only coil embolism or with stent/ balloon remodelling. ACoA occlusion could only be the last resort to some complicated ACoAAs.…”
Section: Discussionmentioning
confidence: 99%